Smart Grid Information Management System Relying on MAS Technology and Complex Scientific Management Thinking - Jing Tong (Discrete Dynamics in Nature and Society)
With the continuous social and economic development, more and more attention has been paid to the safety and efficiency of the power grid. In this paper, the importance and technical support for the informatization and intelligent implementation of the smart grid are explored based on the complex scientific management thinking combined with MAS technology, with the smart grid as the breakthrough point. Subsequently, the framework structure of the smart grid information management system based on multiagent technology is put forward, focusing on expounding the design and functions of agents at the equipment level, subsystem level, and total system level in the system. The system functions are verified and analyzed through the test examples. The practice has proved that the smart grid information management system designed in this paper can provide technical support for smart grid informatization and intelligent implementation.